Struktur Naratif Legenda Telaga Sarangan - Sari Ani (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
This study was made to describe the narrative structure contained in the folklore of Telaga Sarangan. The method used in this research is qualitative research with a naturalistic approach. The theory used is the narrative structure theory of the Maranda model. The results of interviews with informants were used as the main data source in the study. Data collection is in the form of observation, recording, interview and recording methods. The results of the study show that there is a narrative structure that includes the initial plot, middle plot, and ending plot. Keywords: sarangan lake legend, narrative structure